Iatrogenic complications arising from cleaning and shaping : A review - Mehta, Sachin Dev; Malhan, Sunil; Bansal, Chahat (International journal of health sciences, 2021)
Endodontic treatments tend to have very high successful rates in spite of the fact that they are quite an invasive, difficult procedure, especially in complex anatomies. As a consequence, retreatment has become a well-defined field of knowledge and expertise in endodontics, since most complications can be solved with proper surgical or nonsurgical retreatments. Failure to grasp the rationale behind cleaning and shaping concepts can increase the occurrence of needless complications, such as ledges. Extension of the access cavity to provide unobstructed access to the root canals, precurving and not forcing instruments, using NiTi files, using passive step-back and balanced force techniques, and instrumenting the canal to its full length will all help to prevent ledge formation. Initial negotiation and bypassing the ledge can be achieved using a small file with a distinct curve at the tip, whereas a slight rotation motion of the file combined with a picking motion can often help advance the instrument. Blockage, laceration, and foraminal damage are the most common results. Each alters the reliability of the procedure and must be prevented if one is to obtain the best possible prognosis for the patient.